Assessing rural farmers’ willingness to pay for crop insurance scheme: Evidence from Rwanda - Jules Ngango; Fabrice Nkurunziza; Joseph Ndagijimana (Cogent Economics & Finance)
Agriculture plays a significant role in Rwanda’s economic growth but is still highly rain-fed with risks and losses caused by adverse natural and climate shocks. Agricultural insurance schemes are widely recognized as potential risk management strategies. This study aims to examine the determinants of farmers’ willingness to insure maize farms and the premium farmers are willing to pay for crop insurance. The data used in this study were obtained from a household survey conducted in Eastern Rwanda and a sample of 325 households was drawn. A double-hurdle model is used for empirical analysis and the findings show that education, land tenure, farm size, group membership, and insurance awareness have a positive effect on maize farmers’ decision to adopt crop insurance. Regarding the determinants of willingness to pay, education, land tenure, farm size, credit access, and income positively influenced the insurance premium maize farmers were willing to pay whereas household size negatively influenced the premium farmers were willing to pay for crop insurance. The study recommends policy frameworks that strengthen the education in rural communities about the usefulness of crop insurance to enhance farmers’ participation in crop insurance and increase the premium farmers will be willing to pay for crop insurance. Besides, the study highlights the importance of building the capacity of farmers’ groups or cooperatives to promote the uptake of crop insurance as well as the premium to be paid. The study also recommends the improvement of farmers’ access to credit facilities to allow farmers to get the financial capability.